A newsreel history of the Third Reich. Volume 17, D-Day landings [videorecording (DVD)]. (Artsmagic, 2008)
Deals with the first part of the year 1944, covering events on all the German fronts including: Western Front--Rommel inspects the troops and fortifications along the Channel coast; Home Front--preparations in Berlin against bomber raids; Eastern Front--tactical withdrawals around Narva, new front lines established, reinforcements for the front, artillery and troops; Mediterranean Front--Allied troops advance at Monte Cassino.